The Rise of Noncommunicable Diseases in Kenya: An Examination of the Time Trends and Contribution of the Changes in Diet and Physical Inactivity - Edward Michieka Onyango; Benjamin Moranga Onyango (Springer, 2018)
This study examined correlations of historical changes in diet and physical inactivity with the rise of noncommunicable diseases (NCDs) in Kenya. Historical data on diet, wage jobs by industry, urbanization, gross domestic product (GDP), and morbidity due to NCDs were extracted from Kenya Statistical Abstracts, Food and Agriculture Organization (FAOSTAT), and the World Bank online database. These data were plotted and correlations between these factors and the incidence of different NCDs over time were evaluated. There was a rapid rise in the incidence of circulatory disease starting in 2001, and of hypertension and diabetes starting in 2008. The rise of these NCDs, especially hypertension and diabetes, was accompanied over the same period by a rise in per capita GDP and physical inactivity (as measured by increased urbanization and declining proportion of agricultural and forestry wage jobs); a rise in per capita supply of rice, wheat and its products, and cooking oils; and a decline in the per capita supply of maize and sugar. In conclusion, the positive correlations between indicators of dietary consumption and physical inactivity and rates of hypertension, circulatory disease, and diabetes suggest that the rapid rise of NCDs in Kenya may be, in part, due to changes in these modifiable factors.